SINDOOR AND THE STATE: GENDERED SYMBOLISM AND STRATEGIC MASCULINITY IN THE PAKISTAN-INDIA 2025 CONFLICT (Contemporary Journal of Social Science Review, 2025)
This study unfolds gendered and nationally strategic discourse of Pakistan-India 2025 conflict particularly of Operation Sindoor conducted by Indian military. In this context, this paper digs deep into the use of language in constructing discourses of gender, power, and national ideology.  By keeping this in view, it combines Norman Fairclough’s theoretical framework of Critical Discourse Analysis (CDA) with Carol Cohn’s theory of “technostrategic” language and militarized masculinity. This research analyses official tweets and the media headlines that were also tweeted for this purpose. The analysis sheds light on the gendered metaphors of “sindoor”, “mothers and sisters”, and “Bharat mata” as a tool to legitimize strategic militarized masculinity in the form of nuclear strikes and violence by reinforcing social gender ideology. Through the critical analysis of gendered nationalist discourse, this research adds to the study of language and gender, it also contributes to the interdisciplinary studies. It deepens the understanding of language as a weapon in digitally mediated warfare discourse.